2021
DOI: 10.1096/fj.202101566r
|View full text |Cite
|
Sign up to set email alerts
|

Targeting lysine‐specific demethylase 1A inhibits renal epithelial–mesenchymal transition and attenuates renal fibrosis

Abstract: Lysine‐specific histone demethylase 1 (LSD1) as the first identified histone/lysine demethylase regulates gene expression and protein functions in diverse diseases. In this study, we show that the expression of LSD1 is increased in mouse kidneys with unilateral ureteral obstruction (UUO) and in cultured NRK‐52E cells undergoing TGF‐β1‐induced epithelial–mesenchymal transition (EMT). Inhibition of LSD1 with its specific inhibitor ORY1001 attenuated renal EMT and fibrosis, which was associated with decreased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In addition, it was found that LSD1 expression was abnormally elevated in the serum of CHF patients and AngII-induced HCFs. A previous study showed increased expression of LSD1 in the kidney of mice with unilateral ureteral obstruction and TGF-β1-induced NRK-52E cells and inhibition of LSD1 using a specific inhibitor, ORY1001, alleviated renal epithelial-to-mesenchymal transition and fibrosis (25). In bleomycin-induced pulmonary fibrosis mice and lung tissues of TGF-β1-treated lung fibroblasts, LSD1 expression was elevated and LSD1 activation promoted differentiation and fibrosis of lung myoblasts by targeting the TGF-β1/Smad3 signaling pathway (26).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it was found that LSD1 expression was abnormally elevated in the serum of CHF patients and AngII-induced HCFs. A previous study showed increased expression of LSD1 in the kidney of mice with unilateral ureteral obstruction and TGF-β1-induced NRK-52E cells and inhibition of LSD1 using a specific inhibitor, ORY1001, alleviated renal epithelial-to-mesenchymal transition and fibrosis (25). In bleomycin-induced pulmonary fibrosis mice and lung tissues of TGF-β1-treated lung fibroblasts, LSD1 expression was elevated and LSD1 activation promoted differentiation and fibrosis of lung myoblasts by targeting the TGF-β1/Smad3 signaling pathway (26).…”
Section: Discussionmentioning
confidence: 98%
“…According to reports, the acetylation of histone lysine is associated with myocardial remodeling ( Peng et al, 2021 ; Han et al, 2022 ), and the lysine methylation of histone promotes the reprogramming of myocardial cells by fibroblasts ( Singh et al, 2021 ). Meanwhile, histone lysine-specific demethylase one induced renal fibrosis ( Dong et al, 2022 ; Zhang et al, 2022 ). However, a large increase in lysine was observed in the abdominal radiation group of this study, combined with the enrichment of other metabolites concentrated in the lysine metabolic pathway, further indicating that the large accumulation of lysine, but its role in the changes in cardiac structure and function is still need further verification.…”
Section: Discussionmentioning
confidence: 99%
“…Lysine-specific demethylase 1 (LSD1), also known as KDM1A, is the first histone/lysine demethylase that specifically targets mono- and dimethylated H3K4 [ 142 ]. The upregulation of LSD1 was involved in renal tubular cell EMT, deposition of ECM proteins, and renal fibrosis progression in UUO model mice [ 143 ]. This was confirmed through the use of specific inhibitors or siRNA targeting LSD1, which reduced TGF-β1-induced EMT and blocked the activation of renal fibroblasts through TGF-β1/Smad3 and LSD1/PKC/α-Akt/STAT3 signaling pathways [ 143 ].…”
Section: Epigenetics Regulation Of Emp/emt-dependent Fibrosismentioning
confidence: 99%